Construction of Vesicles, Micro/Nanorods and Ultralong Nanotubes through the Self‐Assembly of Non‐Classical Amphiphiles with Rigid Conformation. Issue 4 (10th April 2017) - Lin, Feng; Liang, Rongran; Qi, Qiaoyan; Zhan, Tianguang; Li, Zhanting; Zhao, Xin
Abstract: Amphiphilic molecules have long been regarded as an important class of supramolecular building blocks for the fabrication of nanomaterials. While most previous researches have mainly focused on amphiphlies with flexible structures, in this work, four novel amphiphiles possessing wholly‐rigid skeletons have been designed and synthesized. These molecules were built by using 4, 4'‐bipyridin‐1‐ium or viologen as hydrophilic moieties and phenyl or biphenyl as hydrophobic segments, bridged by a pyridazine unit. Their self‐assembly behavior has been investigated by scanning electron microscopy (SEM), atomic force microscopy (AFM) and transmission electron microscopy (TEM), which revealed they could self‐assemble into well‐ordered nanoarchitectures with various morphologies such as vesicles, micro/nanorods and nanotubes in water or methanol, depending on their hydrophilic/hydrophobic fraction ratios. Abstract : Four novel amphiphiles possessing wholly‐rigid skeletons have been designed and synthesized. They self‐assembled into well‐ordered nanoarchitectures with various morphologies such as vesicles, micro/nanorods and nanotubes in water or methanol.